2021
DOI: 10.1158/1535-7163.mct-21-0221
|View full text |Cite
|
Sign up to set email alerts
|

TPX-0131, a Potent CNS-penetrant, Next-generation Inhibitor of Wild-type ALK and ALK-resistant Mutations

Abstract: Since 2011, with the approval of crizotinib and subsequent approval of four additional targeted therapies, ALK inhibitors have become important treatments for a subset of patients with lung cancer. Each generation of ALK inhibitor showed improvements in terms of CNS penetration and potency against wild-type ALK, yet a key continued limitation is their susceptibility to resistance from ALK active-site mutations. The solvent front mutation (G1202R) and gatekeeper mutation (L1196M) are major resistance mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 20 publications
2
34
0
Order By: Relevance
“…L1196M + G1202R, a major repotrectinib-resistant mutation, is also discovered to be a lorlatinib-resistant mutation 13 . This mutant is highly resistant to all approved ALK-TKIs; however, we confirmed that a novel ALK-TKI, TPX-0131, was potent to this mutant 27 . If the efficacy and safety of TPX-0131 were demonstrated in a current clinical trial, this inhibitor would be an excellent treatment option for repotrectinib-resistant patients with the L1196M + G1202R mutation.…”
Section: Discussionsupporting
confidence: 59%
“…L1196M + G1202R, a major repotrectinib-resistant mutation, is also discovered to be a lorlatinib-resistant mutation 13 . This mutant is highly resistant to all approved ALK-TKIs; however, we confirmed that a novel ALK-TKI, TPX-0131, was potent to this mutant 27 . If the efficacy and safety of TPX-0131 were demonstrated in a current clinical trial, this inhibitor would be an excellent treatment option for repotrectinib-resistant patients with the L1196M + G1202R mutation.…”
Section: Discussionsupporting
confidence: 59%
“…The fourth-generation ALK-TKIs are currently considered the most promising treatment for compound ALK mutation. Two fourth-generation ALK TKIs (TPX-0131 and NVL-655) are under development [ 88 , 89 , 90 , 91 ]. Both TPX-0131 and NVL-655 can inhibit acquired compound ALK mutations in addition to a wide spectrum of single ALK mutations.…”
Section: Mechanism Of Resistance Against Alk-tkimentioning
confidence: 99%
“…Fourth-generation ALK TKIs such as TPX-0131 and NVL-655 have been developed, which are “double mutant active.” TPX-0131 is a compact macrocyclic inhibitor, which was designed to fit completely in the ATP-binding pocket. It may reduce the susceptibility to a variety of ALK TKI-resistant mutations, including solvent front, hinge region, gatekeeper, and compound mutations ( 82 ). Other than being sensitive to most single resistant mutations, TPX-0131 is effective for compound mutations such as G1202R+L1198F, G1202R+L1196M, L1196M+ L1198F, and G1202R+C1156F.…”
Section: Alk Targeted Therapies In Nsclcmentioning
confidence: 99%